META-ANALYSIS: AUDIT QUALITY DETERMINANTS - Ayu Ambang Lestari; Helianti Utami; Bambang Sugeng (International Journal of Economy, Education and Entrepreneurship, 2022)
This research aims to identify the results of empirical research related to the determinants of audit quality and to show a deep understanding of the reasons behind the differences in the results of previous studies. This study uses a meta-analysis with a sample of 45 international studies from original scientific articles from the years 2003 to 2020. The results showed that audit firm size and independence had a significant positive effect on audit quality. Meanwhile, audit tenure and industry specialization have a non-significant positive impact on audit quality. Furthermore, the analysis results also prove that the classification of countries (developed and developing) can moderate the relationship between audit firm size, independence, audit tenure, and industry specialization in audit quality